COMMUNICATION STRATEGIES IN PREVENTING NON-PROCEDURAL INDONESIAN MIGRANT WORKERS STUDY EXAMPLE AT SURABAYA IMMIGRATION OFFICE - Koesmoyo Ponco Aji; Mochammad Ryanindityo; Wildan Hariz Juliano (Polteknik Imigrasi, 2023)
Indonesian Migrant Workers, travel documents are required as a condition for working abroad. There are problems that arise when they want to work abroad, the trigger for this is that many people have not received information to become Indonesian Migrant Workers, so there are many phenomena to work abroad non-procedurally. A research is needed regarding the communication strategies carried out in disseminating information to prevent the occurrence of non-procedural Indonesian migrant workers, as well as the obstacles faced in disseminating information. By using qualitative research methods, this research was carried out using the theory of communication strategies including knowing the audience, compiling messages, determining methods and selecting and using media. By conducting observations and direct interviews with sources to obtain data. The results of this study indicate that by implementing a communication strategy in disseminating information by direct socialization and using social media, mass media, and print media to Indonesian Migrant Workers candidates. The communication strategy carried out by the Class I Immigration Office for Immigration Checkpoint (IC) Surabaya has met the criteria for indicators in the theory of communication strategy but there are obstacles in the use of the method. To maximize the use of the method, it is possible to establish a Village Entry Immigration (VEI) program to be able to carry out regular socialization activities in every sub-district, and areas that are considered Indonesian migrant workers barns.